The Productivity, Economic Structure and Middle-income Trap— Can China Avoid this Trap? - Chen, Yueyun(Bill); Yu, Liping; Pu, Chengyi; Lin, Lianlian (Journal of Applied Business and Economics, 2017)
This paper establishes an economic model to directly study the effects of the labor ratio, economic structure and productivity of a country on its economic growth. The model analysis also indicates the relevancy and importance of the stable exchange and inflation rates to the economic success of a nation. Using data from selected countries over the particular years, this paper explores and explains why some economies have successfully passed through the middle-income trap, while others fell in. The paper then compares China’s relevant data with that of others, and discusses challenges and problems China faces and how it can avoid this middle-income trap.